Perubahan Emosional dan Psikologis Pada Ibu Hamil - Mutiara Megasari Mattalitti; Sayidah Aulia Ul Haque (Journal of Innovative and Creativity, 2025)
ABSTRACT The purpose of this study was to examine emotional changes among pregnant women in Kelurahan Dupak, Surabaya, and to implement a psychoeducational intervention designed to improve emotional awareness and self-regulation during pregnancy. This community-based psychological program aimed to identify psychological issues associated with pregnancy—such as mood instability, anxiety, and emotional confusion—and to strengthen mothers’ mental health literacy and coping abilities through preventive education in primary care settings. Materials and Methods. This study adopted a mixed qualitative and quantitative approach through interviews, observations, Focus Group Discussions (FGD), and psychological screening using the Edinburgh Postnatal Depression Scale (EPDS). Twenty-eight pregnant women aged 19–38 participated, and ten of them scored ≥13 on the EPDS, indicating symptoms of prenatal anxiety or depression. The intervention consisted of psychoeducational sessions on emotional changes, triggers, and self-regulation strategies, including stress awareness and relaxation practices. Data were analyzed using descriptive statistics and paired sample t-tests to measure changes in understanding and emotional management. Results. The findings revealed that most participants experienced emotional instability, excessive worry, and difficulty managing stress due to hormonal changes, cultural expectations, and limited mental health knowledge. Post-intervention data showed a significant improvement in understanding emotional regulation, with post-test mean scores (M = 8.5) higher than pre-test (M = 4.0), t(9) = –12.075, p = 0.000. Participants reported feeling calmer, more supported, and more confident in expressing emotions. Conclusions. Psychoeducational interventions effectively enhanced maternal emotional awareness and reduced anxiety during pregnancy. Integrating mental health education into maternal programs, involving partners, and encouraging routine psychological screening are recommended to support sustainable community mental health. Keywords: Emotional changes, psychoeducation, pregnancy, anxiety, maternal mental health